Strategi Optimalisasi Pengelolaan Sumber Daya Perikanan dan Kelautan Daerah - Sa'adah, Muhimmatus (Jurnal Administrasi Publik, 2013)
Abstract: Lamongan has potential fisheries and marine who served in the strategic national development and as the driving force of economic growth as a provider of food, a provider of employment, industrial raw material providers, a source of foreign exchange and environmental sustainability. However, the utilization of fishery resources and marine lamongan is still not optimal, where a lack of management of these resources. The purpose of this research was to know what strategy taken by the marine and Fisheries Agency in managing fisheries resources optimally as well as supporting factors and the barrier. The research method used is descriptive research with qualitative approach. Research results explain the strategy taken by the Government which include human resource development, development of facilities and infrastructure, program development fisheries and marine resources. As well as supporting factors in fisheries resource management strategy and marine is the existence of resources and marine fisheries. Factor inhibitor, with limited facilities and infrastructure as well as the poor quality of human resources. Keywords: Livable housing, Abstrak: Kabupaten Lamongan memiliki potensi perikanan dan kelautan yang berperan strategis dalam pembangunan nasional dan sebagai penggerak pertumbuhan ekonomi sebagai penyedia bahan pangan, penyedia lapangan kerja, penyedia bahan baku industri, sumber devisa dan penjaga kelestarian lingkungan. Akan tetapi pemanfaatan sumber daya perikanan dan kelautan kabupaten lamongan masih belum optimal, dimana kurangnya pengelolaan terhadap sumber daya tersebut. Tujuan dari penelitian ini untuk mengetahui strategi apa yang diambil oleh dinas perikanan dan kelautan dalam mengelola sumber daya perikanan secara optimal serta faktor-faktor pendukung dan penghambat. Metode penelitian yang digunakan adalah penelitian deskriptif dengan pendekatan kualitatif. Hasil penelitian menjelaskan strategi yang diambil oleh pemerintah yang meliputi pengembangan sumber daya manusia, pengembangan sarana dan prasarana, program pengembangan sumber daya perikanan dan kelautan. Serta faktor pendukung dalam strategi pengelolaan sumber daya perikanan dan kelautan adalah adanya sumber daya perikanan dan kelautan. Faktor penghambat, terbatasnya sarana dan prasarana serta rendahnya kualitas sumber daya manusia. Kata kunci: Peran Pemerintah, Potensi pesisir